2022
DOI: 10.54847/cp.2022.03.17
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of intraoperative voiding cystourethrogram as an indicator of sucess in the endoscopic treatment of vesicoureteral reflux

Abstract: Objective. Up until now, serial voiding cystourethrogram (SVCU) has been regarded as the gold standard technique in the diagnosis of vesicoureteral reflux (VUR). The aim of intraoperative SVCU during endoscopic treatment is to detect those patients eligible to receive more biosynthetic material as a result of persistent VUR. The objective of this study was to assess the usefulness of SVCU as a predictor of treatment success.Materials and methods. An analytical, retrospective study of patient medical records wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 14 publications
2
2
0
Order By: Relevance
“…In most of the studies found in the international literature on endoscopic treatment of VUR, a predominance of the female gender is reported, which coincides with the results of the present investigation 13,14,15,16,17,18,19,20,21 .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In most of the studies found in the international literature on endoscopic treatment of VUR, a predominance of the female gender is reported, which coincides with the results of the present investigation 13,14,15,16,17,18,19,20,21 .…”
Section: Discussionsupporting
confidence: 92%
“…Regarding the laterality of reflux, several authors report a predominance of bilateral VUR in patients undergoing endoscopic treatment. The results of the present investigation correspond with those of these authors 13,14,16,18,19 .Others report a predominance of unilateral VUR 17,23 .…”
Section: Complicationssupporting
confidence: 93%
See 2 more Smart Citations